Leader power and interpersonal conflict: The mediating effects of management communication style in government link companies, Malaysia / Rozilah Abdul Aziz - Abdul Aziz, Rozilah (Institute of Graduate Studies, UiTM, 2018)
In a complex and fast-changing business environment, it is evidenced that managers are faced with multitudes of problems in the organizational setting. One of the never ending problems faced by managers is interpersonal conflict that occurs between individuals or groups in organizations that emphasizes the interaction of human factors in an organization. In order to circumvent conflicts that transpire among the employees, most organizations have emphasized on effective communication that are most likely to improve the employee own chances to survive and prosper in organizations. Review of related international literatures revealed the importance of communication style in decision making, nevertheless, there is lack of empirical evidence to support this in the Malaysian context and this study contributes deeper understanding of some of the critical aspects of management communication style. Using a research framework constructed from adaptation of two key power models: Lusch Model (1976) and Richmond, McCroskey, Davis and Koontz's Theory (1980), this study explores the argument that management communication style (tell, sell, consult and join) interpersonal conflict (task conflict and relationship conflict) are influenced by leader power (referent, coercive, expert, legitimate and referent). In particular, this study seeks to investigate the mediating effects of management communication style on the relationship between leader power an interpersonal conflict. Thus, it presents and discusses empirical findings from data collected from 388 executives working directly under HR Managers in GLCs, Malaysia applying Structural Equation Modeling (AMOS Version 20) and Statistical Package or Social Science (SPSS Version 20)…